Luteolin Treatment Protects against Renal Ischemia-Reperfusion Injury in Rats - Xin Hong; Xiaojing Zhao; Gang Wang; Zhengliang Zhang; Honghong Pei; Zhong Liu (Hindawi Limited, 2017)
Renal ischemia-reperfusion (I/R) injury is a common but severe scientific problem. Luteolin has great anti-inflammatory and antioxidant effects. In this study, we studied the effect of luteolin on renal I/R injury in rats. Intragastric administration of luteolin or saline was performed in Sprague-Dawley rats before (40 mg/kg for three days) and after (one day) renal I/R modeling. Kidney and blood samples were harvested to detect the severity of renal injury 24 hours after operation. The results showed that luteolin-treated rats exhibited milder histomorphological changes with lower scores of renal histological lesions; lower blood urea nitrogen and creatinine levels; lower renal malondialdehyde (MDA), 8-oxo-deoxyguanosine (8-OHdG), and myeloperoxidase (MPO) levels; and higher superoxide dismutase (SOD) and catalase (CAT) activities in the kidney. Luteolin attenuated the increased levels of serum and renal tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6, renal high mobility group box-1 (HMGB1), and nuclear factor kappa β (NF-κB) expression levels in I/R rats. Furthermore, luteolin treatment significantly reduced renal cell apoptosis and endoplasmic reticulum (ER) stress caused by renal I/R injury. In conclusion, luteolin improved renal function in I/R rats by reducing oxidative stress, neutrophil infiltration, inflammation, renal cell apoptosis, and expression of HMGB1 and NF-κB, and ER stress.